BUILDING SELF-RELIANCE OF PACKET C GRADUATES THROUGH ABG-C (ACADEMIC, BUSINESS, GOVERNMENT AND COMMUNITY) THROUGH LOCAL POTENTIALS AT PKBM ASSOLAHIYAH - Heru Saleh; Syaepudin Syaepudin; Lince Sari Dianawati Leatemia (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2020)
This study goals to explore how self-reliance can be built from local potentials and how it could improve the quality of PKBM Assolahiyah (The PKBM)’s process, to find out how effective ABG-C strategies might correlate with local potentials and be applicable to The PKBM, and to discover the results of the ABG-C strategy based on local potentials on The PKBM. Furthermore, this study is also to find out the strengths and weaknesses of ABG-C strategies. This study used a qualitative descriptive method by using observation guideline data collection, interview guidelines, documentation, and literature studies with informants as many as 6 people: 1 PKBM manager and 5 study residents. The results showed that building the self-reliance of education graduates in Packet C program through ABG-C strategy based on local potential existence of The PKBM for Karawang Regency community was interpreted as a complement to formal education institutions by local communities to be able to change their lives become more empowered. The study of the results of the implementation of ABG-C strategies based on local potential in the The PKBM, can be traced by looking at the application of PKBM principles and the concept of adult education (andragogy), in the running of the education system from the PKBM refers to the application of the principles adopted by the PKBM, including: the principle of benefit, the principle of meaningfulness, the principle of togetherness, the principle of self-reliance, the principle of harmony, the principle of need, the principle of helping. The conclusion of this study is to build the self-reliance of education graduates of Packet C program through ABG-C strategy based on local potential The PKBM basically includes four stages: the process of self-reliance, strategy, results and advantages, and weaknesses of the ABG-C strategy based on local potential. The four stages of each other have relevance and continuity in the learning process so that in the end it can contribute to the knowledge, attitudes and skills of the learning community.